The evaluation of sheltered workshops by employed personnel with disabilities - Czerwiak, Grażyna M.; Trela, Roman (Medical Studies/Studia Medyczne, 2015)
Introduction : Disability is a complex concept with different dimensions associated with functional limitations of an individual and/or environment. From one point of view, scientific and technological progress increases the chances of being active in professional life, yet it requires high professional qualifications. Aim of the research : The aim of the study was to investigate the employment character in those workshops. The theme of the research was the assumption that the process of rehabilitation of disabled persons is achieved in a complex social system. Material and methods: A diagnostic survey with the use of a customised questionnaire was carried out in November/December 2013 among 108 persons with disabilities employed in sheltered workshops in the Świętokrzyskie Province. Results : The most common causes of disability among the respondents were the locomotor system, neurological, respiratory, and circulatory diseases. The obstacles in establishing interpersonal contacts would include the fear of negative feedback in their close environment, the lack of knowledge in society about disability, architectural barriers, and appearance. The disabled expected both economic and informative support. Conclusions : The activity of persons with disabilities depends on employment opportunities in the labour market, but also on the candidate’s education, age, and their degree of disability. The sheltered workshops reinforce the sense of economic security and social ties, whereas employment itself brings a particularly appreciated value for this population.